The Connection between Green Space and Cardiovascular Health in Winter City of Harbin, China - Luan Yunqi, Trifonova Tatiana, Goncharov Vladimir, Guo Peng (Forest Chemicals Review, 2022)
Severely cold climates have a significant impact on cardiovascular health. Studies have shown that green space, as an important health resource, can play a positive role in promoting cardiovascular health through the air environment and exercise. There are few studies on the correlation between urban green spaces and cardiovascular health in winter. In this study, Harbin was used as an empirical case and representative community samples were selected to explore the correlation between community green spaces and cardiovascular health. The results showed that the characteristics of green spaces in residential areas were related to cardiovascular disease and its risk factors. In communities with a green space ratio of less than 28%, residents are at higher risk of lack of exercise, overweight or obesity, high blood pressure and stroke. In communities with a green view index of less than 15%, residents have a higher risk of insufficient physical activity, overweight/obesity, high blood pressure, dyslipidemia, and stroke. There are also significant differences in the cardiovascular health scores of residents in communities with different green space characteristics. Emphasizing the importance of effectively increasing the ratio of community green spaces and the green landscape index to reduce the risk of cardiovascular disease may be of benefit to intervention efforts.